Estudo comparativo entre o aquecimento ôhmico e convencional aplicado em polpa de goiaba vermelha - Giuliangeli, Vanessa Cipriani (2021)
Ohmic treatment is an emerging technology that has been studied for application in food heat treatment. The main benefit associated with the process is the possibility of heating materials quickly and evenly, including particulate products such as fruit pulps. This work aimed to apply conventional and ohmic heat treatment to red guava pulp, aiming to study the influence on the content of ascorbic acid, carotenoids, and color variation. Additionally, the thermal efficiency and the pasteurization value (P) of both treatments were calculated. The guava pulp was initially characterized in terms of pH, total soluble solids, total titratable acidity, color, ascorbic acid, and carotenoid content. Conventional and ohmic heat treatment were carried out at temperatures of 60, 70 and 80 °C for 110 minutes. During the process, pulp samples were collected to determine the concentration of ascorbic acid and carotenoids and measurement of the color. The ascorbic acid concentration data were adjusted in kinetic models (zero, first, second-order and Weibull) and with the kinetic data the thermodynamic parameters (activation energy, enthalpy variation, entropy and Gibbs energy) were determined. According to the heat transfer process, the ohmic treatment showed a thermal efficiency of 40.93 %, while the conventional one was 2.62 %. Among the kinetic models tested and according to the statistic parameters used, the first order model showed the best fit to the decay of ascorbic acid. The degradation rate of ascorbic acid was proportional to the temperature of the heat treatment, being an order of magnitude higher for the ohmic heating compared to the conventional treatment. The degradation of ascorbic acid occurred in greater proportion with the ohmic treatment and may have occurred due to the low pH of the pulp (3.98) and the use of the low frequency of the electric field. Comparatively, in the thermal treatment at 60 ºC there was a greater retention of carotenoids which may be due to the lower temperature and disruption of the cellular matrix and release into the medium. Regarding the guava pulp color, it was found that there was no significant change for both treatments. P was reached faster with ohmic heating and the higher P, the greater the degradation of ascorbic acid. Thus, the results obtained in the present work demonstrated that the ohmic heating can be seen as a potential technology for the thermal treatment of the guava pulp regarding the retention of carotenoids, color, energy saving and interesting for the unit operation of pasteurization, or heating , since the energy conversion is more efficient, ecologically correct, as it contributes to the reduction of fuel consumption and emissions related to combustion, in addition to consuming less water to meet sanitary hygiene standards, because in this form of thermal treatment involves a smaller contact surface for the occurrence of fouling and in terms of energy it provides a high energy saving compared to conventional heating.